1969
DOI: 10.3181/00379727-132-34201
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Acetoacetate Condensate II. Isolation and Identification from Human Diabetic Urines

Abstract: Previous work in our laboratories indicated that the condensation product of D-glucosamine and ethyl acetoacetate, ethyl 2-methyl-5 -( D-arabinotetrahydroxybutyl) -3 -py r r ole carboxylate (pyrrole condensate) ( 1 ) , acts as an antialloxan-diabetes factor (2). Also chromatographic evidence for the presence of the pyrrole condensate in the human diabetic urine was found. Its isolation and identification became the next goal in our research studies.Materials and Methods At least 75 ml of urine is refrigerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Presently, the only indirect evidences that we have stabilized connecting pyrrolecondensate with human diabetes are: Its isolation from human diabetic urine (Padron et al, 1969) and the presence of larger amounts of bound glucosamine in the diabetic urine than in the normal urine (Padron et al, 1967). Also glucosamine, one of the components of the pyrrole-condensate, has been found by Stary et al (1950) to be subject to changes in both diabetes mellitus and experimental alloxan diabetes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Presently, the only indirect evidences that we have stabilized connecting pyrrolecondensate with human diabetes are: Its isolation from human diabetic urine (Padron et al, 1969) and the presence of larger amounts of bound glucosamine in the diabetic urine than in the normal urine (Padron et al, 1967). Also glucosamine, one of the components of the pyrrole-condensate, has been found by Stary et al (1950) to be subject to changes in both diabetes mellitus and experimental alloxan diabetes.…”
Section: Discussionmentioning
confidence: 85%
“…Previous work in our laboratories indicated that the condensation product of D-:glucosamine and ethylacetoacetate, ethyl-2-methyl-5-(D-arabino tetrahydroxybutyl)-3-pyrrole carboxylate (pyrrole-condensate) (Gonzalez and Sanchez, 1965) acts as an antialloxan-diabetes factor in rats (Padron, Sulman and Lewis, 1967) and can be isolated and identified from human diabetic urine (Padron, Chittenden and Lewis, 1969).…”
Section: Introductionmentioning
confidence: 99%